2021
DOI: 10.1108/josm-10-2020-0372
|View full text |Cite
|
Sign up to set email alerts
|

The service triad: an empirical study of service robots, customers and frontline employees

Abstract: PurposeRecent service studies suggest focusing on the service triad consisting of technology-customer-frontline employee (FLE). This study empirically investigates the role of service robots in this service triad, with the aim to understand the augmentation or substitution role of service robots in driving utilitarian and hedonic value and ultimately customer repatronage.Design/methodology/approachIn study 1, field data are collected from customers (n = 108) who interacted with a service robot and FLE in a fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 107 publications
0
34
1
Order By: Relevance
“…Also when accounting for service failures in Model 3, human-likeness does not appear to drive social presence perceptions. This is surprising as previous studies found a positive relationship between the two concepts (Odekerken-Schröder et al 2022).…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…Also when accounting for service failures in Model 3, human-likeness does not appear to drive social presence perceptions. This is surprising as previous studies found a positive relationship between the two concepts (Odekerken-Schröder et al 2022).…”
Section: Discussioncontrasting
confidence: 70%
“…In addition, Barco et al (2020) find that children perceive an anthropomorphic robot as more socially present than a zoomorphic robot. Lastly, with a field study in a restaurant context, Odekerken-Schröder et al (2022) find a positive relationship between anthropomorphism and social presence. Therefore, the present study expects human-likeness to increase a service robot's social presence.…”
Section: Social Presencementioning
confidence: 82%
See 2 more Smart Citations
“…All analyses were performed using SmartPLS version 3.3.2 (Ringle et al, 2021). The partial least squares (PLS) approach was chosen in favor of covariance-based SEM, as PLS is well suited to causal-predictive analyses (Evermann & Tate, 2016;Chin et al, 2020;Hair and Sarstedt, 2021), is robust when data are nonnormally distributed (Hair et al, 2016), and has been widely applied in several recent services-related studies (Bartsch et al, 2021;Odekerken-Schröder et al, 2021).…”
Section: Discussionmentioning
confidence: 99%